2020
DOI: 10.1007/s40430-020-02359-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and penetration of a new W-particle/Zr-based amorphous alloy composite liner

Abstract: In this paper, in order to boost the power of shaped charge, a new type of W-particle/Zr-based amorphous alloy composite liner embedded with a restraining cylinder is designed, which is different from the original shaped charge structure. The inner restraining cylinder divides the charge into two coaxial columns: inner and outer, which changes the flow mode of the material in the liner and improves the utilization rate of explosive charge. For the first time, W-particle/Zr-based amorphous alloy (W/Zr amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…We set fixed constraints around the target plate. The equation of state and parameters of copper, copper-z, and 45# steel are shown in [ 19 ], the strength model of copper and copper-z is Steinberg-Guinan, and the model parameters are shown in Table 2 [ 2 ]. The von Mises strength model is adopted for 45# steel, and the parameters are shown in Table 3 .…”
Section: Numerical Simulation Study On Forming Law Of Scs Linermentioning
confidence: 99%
“…We set fixed constraints around the target plate. The equation of state and parameters of copper, copper-z, and 45# steel are shown in [ 19 ], the strength model of copper and copper-z is Steinberg-Guinan, and the model parameters are shown in Table 2 [ 2 ]. The von Mises strength model is adopted for 45# steel, and the parameters are shown in Table 3 .…”
Section: Numerical Simulation Study On Forming Law Of Scs Linermentioning
confidence: 99%
“…Huang et al designed a K-shaped charge with a double-layer liner consisting of Al/Ni and Cu, and the composite jets created much deeper penetration on steel and concrete targets [ 23 ]. Han et al constructed a tungsten and zirconium alloy liner and showed in experiments that the composite jets achieved much deeper penetration [ 24 ]. Zhang et al found that compared with jets using Cu liner, the Cu-PTFE/Al double-layer liner jet generated a penetration cavity diameter twice as large and a spalling area four times as large [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [12], for example, studied ion transport of background electrolytes and analytes in nanochannels upon applying an external hydrodynamic force. Han et al [13,14] proposed novel designs of nanochannel structure to analyze the impact on the ion concentration of the electrolyte. Liu et al [15] investigated the mechanisms of ion transport through micro-nanochannel interfaces for desalination and micromixing, whereas Gong et al [16] presented numerical simulations of a new microfluidic system based on ICP for purification purposes.…”
Section: Introductionmentioning
confidence: 99%
“…[10] studied ion transport of background electrolytes and analytes in nanochannels upon applying an external hydrodynamic force, and demonstrated that ICP enrichment‐exclusion effects can manifest alongside streaming potentials when fluid transport is driven mechanically (rather than electrically) in finite‐EDL nanochannels. Numerical simulations have also been performed in different geometries, including embedded perm‐selective membranes [11,12] and novel nanochannel structures [13,14]. Liu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation